Decision Support System for Determining Infrastructure Project Priorities Using AHP and TOPSIS Methods in Deli Serdang Regency - Sihotang, Jonhariono; Napitupulu, Dea Okviar Egano (Sean Institute, 2025)
Prioritizing infrastructure projects is a major challenge in regional development planning, particularly when faced with limited resources and complex assessment criteria. This study aims to design a decision support system that can assist policymakers in determining the most deserving infrastructure projects for prioritization. The method used is a combination of the Analytic Hierarchy Process (AHP) to determine criteria weights and the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) to rank alternative projects. Five main criteria are used in this study: cost, urgency, social benefits, land readiness, and conformity with the Regional Medium-Term Development Plan (RPJMD). This study uses simulation data on ten alternative infrastructure projects in Deli Serdang Regency. The AHP results show that urgency (29.9%) and conformity with the RPJMD (25.6%) are the criteria with the highest weights. The consistency value (CR = 0.0333) indicates that the criteria assessment is carried out consistently. Through TOPSIS, it was found that the Health Center B Development project had the highest preference value (0.8176), followed by Terminal I Revitalization and Connecting Bridge E. This study proves that the integration of the AHP and TOPSIS methods is able to provide a rational, transparent, and applicable decision-making framework in the context of regional infrastructure development planning.